Empowering Households and Individuals to Co-produce Positive Health Outcomes : For Quality Care Amidst Infrastructure and Resource Constraints - World Bank Group (World Bank, Washington, DC, 2019)
In the most resource-constrained settings, where the first five years of life represent a critical window of vulnerability, the ability to adopt healthier behaviors in the home can determine whether a child survives and thrives or succumbs to disease before his or her fifth birthday. Too often, families lack the knowledge or resources to provide adequate nutrition to young children, increasing their exposure to infectious disease and creating life-long cognitive and developmental deficits. And while the home should be a safe sanctuary for children, common exposures in the household from poor sanitation to parasitic worms, malaria-carrying mosquitoes, and indoor air pollution can put health at risk. New approaches are needed to help the poorest and most vulnerable families create a safe and nurturing home, building the best possible foundation for their children's futures.